KARAKTERISTIK PERTANGGUNGJAWABAN PIDANA KORPORASI - Adriano, Adriano (Pusat Strategi Kebijakan Hukum dan Peradilan Mahkamah Agung RI, 2016)
This dissertation analyzed for real about characteristics of an entity, either a legal or the nonlegal